Single-stage bone resection and cranioplastic reconstruction: comparison of a novel software-derived PEEK workflow with the standard reconstructive method. Issue 8 (August 2020) - Dodier, Philippe; Winter, Fabian; Auzinger, Thomas; Mistelbauer, Gabriel; Frischer, Josa M.; Wang, Wei-Te; Mallouhi, Ammar; Marik, Wolfgang; Wolfsberger, Stefan; Reissig, Lukas; Hammadi, Firas; Matula, Christian; et al.
Abstract: The combined resection of skull-infiltrating tumours and immediate cranioplastic reconstruction predominantly relies on freehand-moulded solutions. Techniques that enable this procedure to be performed easily in routine clinical practice would be useful. A cadaveric study was developed in which a new software tool was used to perform single-stage reconstructions with prefabricated implants after the resection of skull-infiltrating pathologies. A novel 3D visualization and interaction framework was developed to create 10 virtual craniotomies in five cadaveric specimens. Polyether ether ketone (PEEK) implants were manufactured according to the bone defects. The image-guided craniotomy was reconstructed with PEEK and compared to polymethyl methacrylate (PMMA). Navigational accuracy and surgical precision were assessed. The PEEK workflow resulted in up to 10-fold shorter reconstruction times than the standard technique. Surgical precision was reflected by the mean 1.1 ± 0.29 mm distance between the virtual and real craniotomy, with submillimetre precision in 50%. Assessment of the global offset between virtual and actual craniotomy revealed an average shift of 4.5 ± 3.6 mm. The results validated the 'elective single-stage cranioplasty' technique as a state-of-the-art virtual planning method and surgical workflow. This patient-tailored workflow could significantly reduce surgical times compared to the traditional, intraoperative acrylic moulding method and may be an option for the reconstruction of bone defects in the craniofacial region.